2019
DOI: 10.3389/fonc.2019.00605
|View full text |Cite
|
Sign up to set email alerts
|

Topical Diclofenac Reprograms Metabolism and Immune Cell Infiltration in Actinic Keratosis

Abstract: Background: Melanoma and squamous cell carcinoma of the skin are characterized by an altered glucose metabolism, but little is known about metabolic changes in precancerous skin lesions such as actinic keratosis (AK). Here, we studied the central carbon metabolism and immune cell infiltrate of actinic keratosis lesions before, under, and 4 weeks after treatment with topical diclofenac (Solaraze®). Methods: This study was designed as a prospective, randomized, controlled, mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 47 publications
(62 reference statements)
2
12
0
1
Order By: Relevance
“…Anti-tumor activity of diclofenac has been reported, and clinical trials were claimed (Pantziarka et al, 2016). We recently showed that topical administration of diclofenac in actinic keratosis, a pre-cancerous skin lesion, reduced lactate levels and increased IFNg expression in responders (Singer et al, 2019). In line with this, the data of this study suggest that the main impact of diclofenac on checkpoint therapy is the upregulated IFNg expression in T and NK cells.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Anti-tumor activity of diclofenac has been reported, and clinical trials were claimed (Pantziarka et al, 2016). We recently showed that topical administration of diclofenac in actinic keratosis, a pre-cancerous skin lesion, reduced lactate levels and increased IFNg expression in responders (Singer et al, 2019). In line with this, the data of this study suggest that the main impact of diclofenac on checkpoint therapy is the upregulated IFNg expression in T and NK cells.…”
Section: Discussionsupporting
confidence: 80%
“…In support of this notion, a high glycolytic index negatively correlated with progression-free survival in cancer patients treated with anti-PD1 therapy. As diclofenac targets glucose metabolism not only in murine tumor models and cell lines but also in patients with actinic keratosis (Gottfried et al, 2013;Singer et al, 2019), we tested its impact on the efficacy of checkpoint therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ivosidenib, an inhibitor of IDH1, improves the complete remission rate of IDH1-mutated acute myeloid leukemia with a low frequency of treatmentrelated adverse events in a phase I clinical trial that enrolled 258 patients [206]. In a phase IV clinical trial that enrolled 28 patients, the mechanism of diclofenac in effectively relieving actinic keratosis (a premalignant skin lesion) was well demonstrated, and the effect was largely dependent on modulating the metabolism of local lesions [207]. However, given the heterogeneity of different cancers, successful clinical applications in other cancers cannot be directly and simply applied to treating pancreatic tumors.…”
Section: Clinical Perspectives and Conclusionmentioning
confidence: 99%
“…Diclofenac (2-(2-(2,6-dichlorophenylamino)phenyl)acetic acid, Figure 1 ), also known for its sodium salt sold as Voltaren, is a non-steroidal anti-inflammatory drug widely used for actinic keratosis treatment and can be an adjuvant for basal cell carcinoma, squamous cell carcinoma, and melanoma skin metastases therapy [ 35 , 49 , 50 ].…”
Section: Topical Field Treatmentsmentioning
confidence: 99%
“…Its mechanism of action, although not completely elucidated, could involve the inhibition of cyclooxygenase-1 and -2, enzymes involved in reducing prostaglandin formation from arachidonic acid, which reduces PGE2 synthesis and dysplastic keratinocytes in cancerous lesions [ 31 , 35 , 50 , 51 ]. Additionally, it might interfere with the SHH and Wnt signaling and lead to cancer cell apoptosis and inhibit angiogenesis and proliferation [ 31 , 35 , 50 ].…”
Section: Topical Field Treatmentsmentioning
confidence: 99%